Analisis Wacana Model Van Dijk pada Berita kompas.com Edisi 1-8 November 2024 - Wafiroh, Sa’datun; Asropah, Asropah (GERAM (Gerakan Aktif Menulis), 2025)
This study aims to analyse political reporting on Kompas.com during the period 1–8 November 2024 using Van Dijk's discourse analysis model, which includes the dimensions of macrostructure, superstructure, and microstructure. The method used is a descriptive qualitative approach with critical discourse analysis techniques. Data were obtained from seven political news articles published by Kompas.com during the period, which were analysed to identify main themes, news presentation structures, and language and modality usage. The analysis results indicate that the news articles emphasised narratives of reconciliation and stability, with a dominant narrative supporting the legitimacy of the new government. The choice of language used, such as the terms ‘without resentment’ and ‘strategic cooperation,’ served to reinforce the government's positive image and avoid open conflict. The superstructure of the news was structured in such a way as to reinforce the main message of the dominant political actors, while the microstructure used techniques such as nominalisation and passive sentences to maintain neutrality and avoid presenting sharp criticism. This discussion confirms that the media plays an important role in shaping political discourse through text structure and language choices, which often reinforce the government's narrative without providing space for more critical debate. This research enriches our understanding of the role of the media in shaping public opinion and contributes to critical media literacy.